School Principal Leadership in Addressing Teacher Challenges in the Development of the Independent Curriculum at Elementary Schools: (Kepemimpinan Kepala Sekolah dalam Menangani Tantangan Guru pada Pengembangan Kurikulum Merdeka di Sekolah Dasar) - Dewi Ananda Putri; Muhammad Fajar Hidayat (PT. Berkah Smart Academica, 2024)
The implementation of the Independent Curriculum in elementary schools requires significant adjustments in teachers’ competencies and instructional practices. This situation places school principals in a strategic position to support teachers in addressing various challenges encountered during curriculum development. This study aims to examine the role of principals in overcoming teacher-related obstacles in the development of the Independent Curriculum at the elementary school level. A qualitative approach with a case study design was employed at Ngupasan State Elementary School. Data were collected through observation, interviews, and documentation, with data validity ensured through source and technique triangulation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that principals play multiple roles as educators, managers, administrators, supervisors, motivators, and leaders. The strategies implemented include firm and deliberative decision-making, openness to teachers’ input, instructional guidance, communication with the school committee, motivation and performance support, alignment of programs with the school’s vision and mission, facilitation of teachers’ self-directed learning through the Merdeka Mengajar Platform (PMM), quarterly evaluations, and coordination of school facilities and resources.